Justice, Not Development: Sen and the Hegemonic Framework For Ameliorating Global Inequality - Aram Ziai (Global justice: Theory, Practice, Rhetoric, 2014)
Starting from the merits of Sen’s Development as Freedom, the article also explores its shortcomings. It argues that they are related to an uncritical adoption of the discourse of ‘development’, which is the hegemonic framework for ameliorating global inequality today. This discourse implies certain limitations of thought and action, and the article points out three areas where urgent questions of global justice have been largely ignored by development theory and policy as a consequence. Struggles for justice on a global scale, this is the conclusion, should not take the detour of ‘development’.